Bases para el análisis económico de los sistemas de compliance penal - Goldman, Diego Hernán (2019)
Compliance programs and systems of criminal or administrative liability are being increasingly adopted by different countries as measures meant to reduce the social cost of white collar criminality. However, the legal application of these measures does not always ponder correctly the impacts on common good, the levels of economic activity and the adequate functioning of markets of goods and services. Eventually, this situation can lead to undesired effects, such as the inefficiency of the criminal system, the reduction of economic activity or the arising of obstacles to competition. By taking these circumstances into account, in this paper we will utilize the Economic Analysis of Law to analyze the logic that inspires these legal institutes and the incentives they generate. Our objective is to delineate some parameters that allow legislators, judges, legal advisors and businessmen to evaluate different compliance systems in terms of economic efficiency, generation of wealth and the promotion of competition in markets.